The influence of self-efficacy and perceived organizational support on subjective career success among Maybank employees - Nur Syafinah, Zaki Hashim (2019)
The issue of career success in financial services sector had recently highlighted after seeing the decrease of a job creation that reflected the potential and the existing employees to be multitasking to fulfill the job demand. Besides, they also need to face with high skilled jobs due to the changing of trends and technological advances currently. The purpose of this study is to examine the relationship between self-efficacy and perceived organizational support (POS) towards subjective career success. By using proportionate stratified random sampling and simple random sampling, data was gathered from various level of employees at all Maybank branches in Kelantan. The questionnaires were distributed to 170 Maybank employees in Kelantan and only 117 used for analysis. Results found that self-efficacy and POS are significantly related to subjective career success. The theoretical and practical implications are discussed. Finally, some recommendations for future research and practitioner also are discussed.